2006
DOI: 10.1021/bc060235l
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PKM Linkers on Biodistribution Characteristics of the 99mTc-Labeled Cyclic RGDfK Dimer

Abstract: This report describes synthesis of three new cyclic RGDfK peptide conjugates, HYNIC-PKM-SU016 (PKM = E, K and PEG4), and in vivo evaluation of the impact of PKM linkers on biodistribution characteristics of their ternary ligand complexes [ 99m Tc(HYNIC-PKM-SU016)(tricine)(TPPTS)] in athymic nude mice bearing the MDA-MB-435 human breast cancer xenografts. Results from biodistribution studies show that PKM linkers have minimal impact on the integrin α v β 3 binding capability of radiotracers. Even though they ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(85 citation statements)
references
References 34 publications
3
81
1
Order By: Relevance
“…In the last several years, a variety of pharmacokinetic modifying (PKM) linkers have been used to improve the excretion kinetics of radiolabeled cyclic peptides. In this study, glutamic acid (E) was chosen as a PKM linker [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the last several years, a variety of pharmacokinetic modifying (PKM) linkers have been used to improve the excretion kinetics of radiolabeled cyclic peptides. In this study, glutamic acid (E) was chosen as a PKM linker [27].…”
Section: Discussionmentioning
confidence: 99%
“…111 InCl 3 was obtained from Perkin-Elmer Life and Analytical Sciences (North Billarica, MA). E[c(RGDfK)] 2 and E-E[c(RGDfK)] 2 were prepared according to the procedure described in our previous communications (21,23). The reversed-phase C-18 SepPak cartridges were obtained from Waters (Milford, MA).…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Different amino acids and hydrocarbon linkers displayed profound favorable effects on the receptor-binding affinities and pharmacokinetics of radiolabeled RGD [26], a-MSH peptides [18,20,27], and bombesin [28]. Miao et al [18] reported that introduction of a negatively charged linker (Gly-Glu) between the DOTA and CycMSH peptide sequence decreased the renal uptake by 44 % without affecting the tumor uptake at 4 h post injection.…”
Section: Introductionmentioning
confidence: 99%